Vocational Education Needs and Skill Cultivation Paths of Chinese Silk Culture and Fashion Designs - Wuwei Wang (Textile & Leather Review, 2025)
Chinese silk culture has a long history and occupies an important position in the global textile and clothing industry. However, in the current vocational education system, the inheritance of silk culture and the cultivation of clothing design talents have not yet formed a perfect integration mechanism. How vocational education can find a balance between modern design concepts and traditional craftsmanship, and cultivate professionals with both cultural literacy and technical ability has become an important issue to be solved. The purpose of this study is to analyze the current status of the current vocational education system of clothing design in the inheritance of silk culture and skill cultivation, to explore its problems, and to put forward optimization paths to enhance the matching degree of vocational education to the demand of talents in the silk clothing industry, and to promote the modernization of the application of traditional culture and the development of innovation. This study adopts research methods such as literature analysis, questionnaire survey, expert interviews, and case study analysis to systematically investigate the curriculum, teaching mode, integration of industry and education, and the status quo of the application of digital technology in many domestic vocational colleges and universities, and combines with the opinions of industry experts to put forward targeted optimization strategies. This study systematically analyses the current status of the application of silk culture in vocational education for fashion design and proposes a series of targeted optimization strategies to promote vocational education reform and improve the quality of talent training.